Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/07391102.2018.1461137
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine as a minor groove binder of DNA: molecular docking, molecular dynamics, and multi-spectroscopic studies

Abstract: The interaction mechanism and binding mode of capecitabine with ctDNA was extensively investigated using docking and molecular dynamics simulations, fluorescence and circular dichroism (CD) spectroscopy, DNA thermal denaturation studies, and viscosity measurements. The possible binding mode and acting forces on the combination between capecitabine and DNA had been predicted through molecular simulation. Results indicated that capecitabine could relatively locate stably in the G-C base-pairs-rich DNA minor groo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…It has been demonstrated that the structure of the compounds is one of the most important factors that contribute to the DNA binding affinity. However, some factors of the ligands, including size, geometry, hydrophobicity, and hydrogen-bonding ability, can also influence the overall affinity [57].…”
Section: Uv-vis Absorption Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the structure of the compounds is one of the most important factors that contribute to the DNA binding affinity. However, some factors of the ligands, including size, geometry, hydrophobicity, and hydrogen-bonding ability, can also influence the overall affinity [57].…”
Section: Uv-vis Absorption Spectroscopymentioning
confidence: 99%
“…Fluorescent technique is widely used to obtain significant information regarding the interaction between a compound and a biomacromolecule, such as quenching constant, binding constant, and sites [57,64]. Accordingly, the technique was used to study the interaction between the compounds and DNA.…”
Section: Fluorescence Titrationmentioning
confidence: 99%
“… 44 On the other hand, in the case of groove or other nonclassical modes of binding, the twisting or bending of the double helix leads to a slight reduction of the length of the DNA, as a result of which a slight decrease in the viscosity is observed. 45 Figure S7 clearly displays the relative enhancement of viscosity of the DNA upon incubation with complex 1 . Another notable fact is that after the incremental addition of the complex to DNA, the viscosities of the ctDNA–complex 1 adducts increase following a linear pathway, and the pattern of growth follows that observed during DNA–EtBr conjugation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Generally, for intercalation binding, the insertion of the compound between the base pair increases the length of DNA, which leads to an enhancement of the viscosity of the bare macromolecule . On the other hand, in the case of groove or other nonclassical modes of binding, the twisting or bending of the double helix leads to a slight reduction of the length of the DNA, as a result of which a slight decrease in the viscosity is observed Figure S7 clearly displays the relative enhancement of viscosity of the DNA upon incubation with complex 1 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…A decreased binding constants at high temperatures suggested ABR's dissociation from ABR-ctDNA complex. In general terms a binding constant values in the range 10 6 to 10 8 M −1 suggested a strong binding affinity [29,30]. The binding constant values between ABR and ctDNA(Table 2) indicate a relatively strong binding interaction.…”
Section: Binding Constant and Binding Sitesmentioning
confidence: 89%